Human Cytomegalovirus vMIA Inhibits MAVS Oligomerization at Peroxisomes in an MFF-Dependent Manner - Ferreira, Ana Rita; Gouveia, Ana; Magalhães, Ana Cristina; Valença, Isabel; Marques, Mariana; Kagan, Jonathan C.; Ribeiro, Daniela (Frontiers in Cell and Developmental Biology, 2022)
Upon intracellular recognition of viral RNA, RIG-I-like proteins interact with MAVS at peroxisomes and mitochondria, inducing its oligomerization and the downstream production of direct antiviral effectors. The human cytomegalovirus (HCMV) is able to specifically evade this antiviral response, via its antiapoptotic protein vMIA. Besides suppressing the programmed cell death of infected cells, vMIA inhibits the antiviral signalling at mitochondria by inducing the organelle’s fragmentation, consequently hindering the interaction between MAVS and the endoplasmic reticulum protein STING. Here we demonstrate that vMIA interferes with the peroxisomal antiviral signaling via a distinct mechanism that is independent of the organelle’s morphology and does not affect STING. vMIA interacts with MAVS at peroxisomes and inhibits its oligomerization, restraining downstream signaling, in an MFF-dependent manner. This study also demonstrates that HCMV has developed distinct mechanisms to interfere with the peroxisomal and mitochondrial antiviral responses. vMIA is totally dependent on the organelle’s fission machinery to induce peroxisomal fragmentation, while this dependency is not observed at mitochondria. Furthermore, although we here demonstrate that vMIA is also able to inhibit MAVS oligomerization at mitochondria, our results indicate that this process, such as the whole vMIA-mediated inhibition of the mitochondrial antiviral response, is independent of MFF. These observed differences in the mechanisms of action of vMIA towards both organelles, likely reflect their intrinsic differences and roles throughout the viral infection. This study uncovers specific molecular mechanisms that may be further explored as targets for antiviral therapy and highlights the relevance of peroxisomes as platforms for antiviral signalling against HCMV.